أسباب ظهور الأحاديث الموضوعة وخطرها على الفكر الإسلامي: The Reasons for the Emergence of Fabricated Hadiths and Their Danger to Islamic Thought - Danishfar, Abdul Fatah; Aboamro, Abdulmanan; Bannga Ahmed Ali, Ahmed El-Mogtaba (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2025)
ملخص البحث يهدف هذا البحث إلى دراسة أسباب ظهور الأحاديث الموضوعة وتأثيرها السلبي على الفكر الإسلامي، مع التركيز على أهمية الحفاظ على السنة النبوية من التحريف والتزوير. تبرز البحث في انتشار الأحاديث الموضوعة وما يترتب عليها من تأثيرات سلبية على فهم السنة النبوية، خاصة مع تزايد محاولات بعض الباحثين المعاصرين إنكار الأحاديث الصحيحة بدعوى تعارضها مع العقل، مما يشكل تهديدًا لمكانة السنة النبوية كأصل شرعي في الإسلام. تناول البحث علوم الحديث من حيث أصوله وضوابطه، مع تحليل تأثير الأحاديث الموضوعة على الأفراد والمجتمع الإسلامي. كما استعرض جهود العلماء القدامى والمعاصرين في مواجهة الأحاديث الموضوعة وتبيان خطورتها، مع نقد الظاهرة الحديثة المتمثلة في إنكار الأحاديث الصحيحة استنادًا إلى حجج عقلية غير مدعومة بأدلة علمية. اعتمد البحث على المنهج التحليلي والاستقرائي، حيث تم جمع المعلومات وتحليل أسباب ظهور الأحاديث الموضوعة وأهداف الوضاعين، وتأثير ذلك على الفكر الإسلامي. توصل البحث إلى أن الأحاديث الموضوعة تشكل تهديدًا كبيرًا على الفكر الإسلامي من خلال تشويه معاني السنة النبوية. كما أظهر أهمية دور علماء الحديث في حفظ السنة وتمييز الأحاديث المقبولة. وأوصى البحث بضرورة تعزيز دراسة علوم الحديث في المؤسسات الأكاديمية والالتزام بالمناهج العلمية عند التعامل مع الأحاديث النبوية. ABSTRACT This research aims to investigate the causes of fabricated hadiths (mawdu’at) and their detrimental impact on Islamic thought, with a particular focus on the importance of preserving the Prophet’s Sunnah from distortion and forgery. The study delves into the proliferation of fabricated hadiths and their resulting negative consequences for understanding the Prophet’s Sunnah, especially in light of contemporary attempts by some scholars to deny authentic hadiths on the grounds of alleged contradictions with reason, thereby posing a threat to the status of the Sunnah as a fundamental source of Islamic law. The research explores the science of hadith in terms of its origins and criteria, while analyzing the impact of fabricated hadiths on individuals and Islamic societies. It also reviews the efforts of past and contemporary scholars in confronting fabricated hadiths and exposing their dangers, while critiquing the modern phenomenon of denying authentic hadiths based on rational arguments unsupported by scholarly evidence. Employing an analytical and inductive methodology, the research gathers and analyzes information on the causes of fabricated hadiths, the motives of fabricators, and their impact on Islamic thought. The study concludes that fabricated hadiths pose a significant threat to Islamic thought by distorting the meanings of the Prophet’s Sunnah. It also highlights the crucial role of hadith scholars in preserving the Sunnah and distinguishing authentic hadiths. The research recommends the need to strengthen the study of hadith sciences in academic institutions and to adhere to scientific methodologies when dealing with the Prophet’s hadiths.